Modeling of Regional Development Using a Structural Approach: Principles, Tools and Experience of Their Application - Yu. V. Vertakova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
To solve the priority task of the Russian Federation to ensure the effective socio-economic and sustainable development of the regions, it is necessary to carry out an adequate structural policy, the main purpose of which is to form a rational and balanced structure of the economy that can ensure the effective development of the region’s economy. In this regard, the relevance of modeling regional development using a structural approach is beyond doubt. The purpose of the research is to substantiate the need for a close study of the specifics of the regional structure and the features of its modeling, taking into account General and specific principles, tools and practical experience of their application. Scientific novelty is the study of not only the basic laws, features, principles, tools for modeling the structure of the region, but also the experience of their application in determining the proportions and trends in the development of the region in order to conduct an adequate structural policy. The study used theoretical and empirical methods, in particular: literature review, logical and system analysis, methods of empirical data collection, description, modeling, forecasting and processing of research results. As a result of the study, the authors obtained the following results: a comparative analysis of approaches to the definition of the concept of “region”, “structure of the region”; justified that the structure gives the necessary integrity and defines the main characteristics of the region, allowing to consider it as a complete socio-economic system; classification of types of regional structures; justified that the main quality property of the territory is polystructural. As a conclusion, the authors note that in this regard, there can be no single approach to the description of the structure for modeling regional development. Approbation of the author’s approaches to the structuring of the regional economy is made on the materials of the Kursk region. It showed the adequacy of the developed theoretical provisions and allowed to determine the directions of their further development for the improvement of regional structural policy.